Three dimensional finite element computation of the non-isothermal polymer filling process by the phase field model. (October 2022) - Gao, Puyang
Highlights: The phase field method is first employed to simulate the non-isothermal polymer filling process. The mass conservation property of the non-Newtonian fluid is well guaranteed. The finite element computational framework is developed. Abstract: In this paper, we numerically study the three dimensional non-isothermal non-Newtonian filling process using the phase field method. The Cahn-Hilliard equation is firstly attempted to capture the moving melt front between the Newtonian and non-Newtonian fluid. The governing equations of the flow field are able to be written in a unified form on the basis of phase field parameter. The unified Navier-Stokes equations are decoupled via the splitting scheme and then the traditional FEM and SUPG method are employed to solve the suitable equations. The Cross-WLF model is utilized to describe the variation of the viscosity of the polymer melt in the non-isothermal condition. We take the thin wall rectangular cavity as example and compare with the experimental data to illustrate the convergence, robustness and accuracy of numerical algorithm. In addition, we consider the thin wall cavity with a cylindrical obstacle and analyze the influences of the inlet velocity and the size of the injection gate on the filling process. The numerical results agree well with the experimental data and also exhibit good mass conservation property.